Struktur Tata-Bangunan Di Sekitar Alaman Bolak Selangseutang Pada Permukiman Suku Batak Mandailing Sumatera Utara - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This research analized the concept of the Alaman Bolak Selangseutang location and the pattern of the buildings' arrangement. The conception of Alaman Bolak Selangseutang site and the pattern of buildings arrangement in Mandailing lulu villages are based on three mayor things which also indicates the hierarchy these are (1) Concept of Banua, (2) Belief System on river and sun (3) Condition of local natural & geographical condition. The structure of buildings arrangement based on the concept of Banua, belief system and natural & geographical condition has a standard pattern in macro scale of village which was utilized as the main pattern. It refers to the forming of three zones of area Parginjang , Tonga, and Partoru. The stucture of building arrangement form various structure consisted of two parts